Detecção e caracterização molecular de norovírus em crianças com e sem sintomas de gastroenterite aguda em Vitória-ES - Barreira, Débora Maria Pires Gonçalves (2008)
Noroviruses (NoVs) are a major etiological agent of sporadic acute gastroenteritis worldwide. The aim of this study were to detect, to quantify and to determine the genotype of NoVs from children up to three years old symptomatic (with gastroenteritis) and asymptomatic (without gastroenteritis), in the emergency room of Hospital Infantil Nossa Senhora Glória (HINSG), in Vitória-ES, between February 2003 and June 2004. NoVs were investigated by RT-PCR in a total of 319 fecal specimens from children up to three years old with (n=229) and without (n=90) acute diarrhea. NoVs were quantified by real time RT-PCR, sequenced and genotyped by phylogenetic analysis. NoVs were detected in 17% (40/229) and 13% (12/90) of symptomatic and asymptomatic children, respectively. Five NoVrotavirus A mixed infections were observed in symptomatic children. Out of the 52 positive strains, 51 were grouped as NoV GII and one as GI. Data from sequencing and phylogenetic analyses classified 20 strains into the following genotypes: GII/4 (9/13), GII/3 (1/13), GII/6 (2/13) and GII/14 (1/13) in symptomatic and GII/3 (6/7) and GII/8 (1/7) in asymptomatic children. The median RNA viral loads were 8.39 and 7.15 log10 copies/g of fecal specimens for symptomatic and asymptomatic children, respectively (p=0.011). NoV load was lower when it was present in a mixed infection with rotavirus A (p=0.0005). Vomiting and diarrhea were observed in 97.5% of the positive cases without association with viral load. This study demonstrates a great diversity of NoV strains circulating in this geographic area, and reports GII/8 and GII/14 in the American Continent for the first time. In addition, it confirms GII/4 as the most prevalent genotype in symptomatic children and identified GII/3 in an important frequency, especially in asymptomatic children. Furthermore, preliminary results show that symptomatic patients present a viral load that is significantly greater than asymptomatic children (p=0.011) and suggest that rotavirus A may have a suppressor effect on NoV replication when mixed infection occurs.